Students' gender bias in teaching evaluations - Narissra Punyanunt-Carter; Stacy L Carter (Laureate Education Inc, 2015)
The goal of this study was to investigate if there is gender bias in student evaluations. Researchers administered a modified version of the teacher evaluation forms to 58 students (male=30; female=28) in a basic introductory communications class. Half the class was instructed to fill out the survey about a male professor, and the other half a female professor. Researchers broke down the evaluation results question by question in order to give a detailed account of the findings. Results revealed that there is certainly some gender bias at work when students evaluate their instructors. It was also found that gender bias does not significantly affect the evaluations. The results align with other findings in the available literature, which point to some sort of pattern regarding gender bias in evaluations, but it still seems to be inconsequential.  DOI: 10.18870/hlrc.v5i3.234